Landscape and geochemical features of the territory of the city of Vyzhnytsia, Chernivtsi oblast. - Prysakar, Vitalii; Khodan, Halyna; Dobynda, Iryna (Iasi, 2022)
A significant differentiation of landscape areas and tracts of the territory determines the diversity of its natural geochemical landscapes, which is enhanced by the anthropogenic and man-made load. The latter enhances the geochemical differentiation of geochemical parameters, mainly in places of man-made contact. The territory of Vyzhnytsia, which is located at the junction of two physical-geographical regions of the Carpathian physical-geographical country, has such characteristics.
Keywords: landscape, geochemical zoning, settlement landscape, natural landscape